Kapabilitas Dinamik, Kinerja Inovasi, dan Kinerja Perusahaan Jasa Logistik di Indonesia (Suatu Kerangka Penelitian) - Sudrajat, Darjat (Binus Business Review, 2013)
Market value of logistics services business in Indonesia in 2012 is estimated amount of USD 2.76 billion with an average growth of 12.1% per year. The industry is estimated growth in compound annual growth rate (CAGR) of 9.6% or about Rp2,042 trillion in 2015. The attractive market conditions and business opportunities have not been harnessed yet by local players optimally. On the contrary, one by one the local players have been bankruptcy due to unable to compete with foreign logistics services companies. Based on data of Indonesian Logistics and Forwarder Association (ILFA), it is currently registered about 3,000 members, but about 50% of them are still active, while 50% of them are nonactive and getting problems. Of which are still active, not more than 20 companies are ready to compete with foreign logistics services companies. The problem is especially concerning human resource, networks, technology, and capital competencies. In line with that, the fundamental issues examined in this research are how the relationships of dynamic capabilities, innovation performance, and firm performance conceptually in the logistics service industry in Indonesia. To be able to answer the problems, it is necessary to research theoretically how each relationship of these three aspects in order to obtain a research model or framework. Thus the research framework can be used as a reference to construct hypotheses for further research. Based on the literature study, it can be concluded that dynamic capabilities directly affect innovation performance, in which the variables of dynamic capabilities encompass adaptive capabilities, absorptive capabilities, and innovative capabilities. In addition, dynamic capabilities can also directly affect the firm performance but can also indirectly impact on firm performance through innovation performance.